2023
DOI: 10.3390/vaccines11020389
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Parents Taking Their Children for Scheduled Vaccinations during COVID-19 Pandemic in South Africa

Abstract: Scheduled or routine childhood vaccinations are known for their effectiveness in eradicating fear for many life-threatening and disabling diseases and saving lives globally. This paper is aimed at assessing determinants of parents taking their children for scheduled vaccinations during the COVID-19 pandemic in South Africa. Data used for this paper were obtained from the Human Sciences Research Council’s (HSRC) COVID-19 Online Survey titled “One Year Later Survey”, which was conducted between 25 June and 11 Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…However, as in many developing countries, the majority of the population do not take influenza vaccinations (32). Moreover, Makoae et al (33) found that South African parents who had never taken an influenza vaccine were significantly less likely to have taken their children for their scheduled vaccinations. Perceptions of vaccines being beneficial for protecting communities was strongly associated with hesitancy, but particularly so with unwillingness to take the vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…However, as in many developing countries, the majority of the population do not take influenza vaccinations (32). Moreover, Makoae et al (33) found that South African parents who had never taken an influenza vaccine were significantly less likely to have taken their children for their scheduled vaccinations. Perceptions of vaccines being beneficial for protecting communities was strongly associated with hesitancy, but particularly so with unwillingness to take the vaccination.…”
Section: Discussionmentioning
confidence: 99%